2018
DOI: 10.1002/ece3.4116
|View full text |Cite
|
Sign up to set email alerts
|

When beggars are choosers—How nesting of a solitary bee is affected by temporal dynamics of pollen plants in the landscape

Abstract: Wild bees are declining in intensively farmed regions worldwide, threatening pollination services to flowering crops and wild plants. To halt bee declines, it is essential that conservation actions are based on a mechanistic understanding of how bee species utilize landscapes. We aimed at teasing apart how foraging resources in the landscape through the nesting season affected nesting and reproduction of a solitary bee in a farmland region. We investigated how availability of floral resources and potentially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…The number of brood cells per nest was counted as a proxy for nesting success. We did not use the amount of holes used in a trap nest (as proxy for the number of nesting females) or the number of cells per hole (as proxy for reproduction per nesting female), because one female could also construct more than one nest (Persson et al ., ) and we did not monitor the nests frequently (Williams & Kremen, ; Persson et al ., ). The pollen in each nest was harvested and stored together in a 50‐ml tube per nest at −20°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of brood cells per nest was counted as a proxy for nesting success. We did not use the amount of holes used in a trap nest (as proxy for the number of nesting females) or the number of cells per hole (as proxy for reproduction per nesting female), because one female could also construct more than one nest (Persson et al ., ) and we did not monitor the nests frequently (Williams & Kremen, ; Persson et al ., ). The pollen in each nest was harvested and stored together in a 50‐ml tube per nest at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…They found that pollen diversity was higher in trap nests situated in heterogeneous landscapes compared with more simplified landscapes with less diverse floral resources. There are only a few studies about the impact of land use and landscape structures on the foraging behaviour of O. cornuta , but the foraging behaviour of other Osmia species was already studied in a landscape context (Williams & Kremen, ; Persson et al ., ). The aim of this study is to evaluate available pollen resources for O. cornuta in regions of differing land use types (agriculture, viticulture, urban, and village‐structured) in eastern Austria.…”
Section: Introductionmentioning
confidence: 97%
“…), horse chestnut (Aesculus hippocastanum) and buttercup (Ranunculus sp.) and on nectar from diverse floral sources, mainly Rosaceae (including fruit trees) and Brassicaceae (including oilseed rape) [61][62][63][64][65][66]. The collected pollen and nectar are mixed by females in a pollen loaf and served as food for a brood, referred to as larval (food) provision.…”
Section: Experimental Bee Speciesmentioning
confidence: 99%
“…Traditionally, pollen analysis is based on manual microscopy, which requires skilled experts and is labour‐intensive (e.g. Beil et al., 2008; Persson et al., 2018; Wood et al., 2017). Methods include both bright field and dark field microscopy, and can be combined with different pollen preparation methods such as staining of fresh pollen or acetolysis (Kearns & Inouye, 1993), with the latter also possible to use on fossil pollen (Bourel et al., 2020).…”
Section: Introductionmentioning
confidence: 99%